Thyroid Hormone in Hepatocellular Carcinoma: Cancer Risk, Growth Regulation, and Anticancer Drug Resistance - Lin, Yang-Hsiang; Lin, Kwang-Huei; Yeh, Chau-Ting (Frontiers in Medicine, 2020)
Thyroid hormone (TH) and its receptor (TR) are involved in differentiation, metabolic process and growth regulation in hepatocellular carcinoma (HCC). The TH/TR complexes are ligand-dependent transcriptional factors, functioning through binding to thyroid hormone response elements (TRE) upstream of the target genes. To date, deciphering the biological effects of TH in cancer progression remains challenging. Several lines of evidence suggest a growth inhibitory effect of TH in liver cancer. Mutation and aberrant expression of TRs are highly correlated with several types of cancers including HCC. Several reports show that TH inhibits cell growth in liver cancer through regulation of cell cycle-related genes and non-coding RNAs. A case-control study indicates that hypothyroidism is associated with an increased risk of HCC. Moreover, TH/TR suppresses hepatocarcinogenesis via selective autophagy. Conversely, other groups have indicated that TH promotes cancer cell proliferation. In vitro and in vivo experiments show that TH/TR enhances cancer cell migration and invasion, anticancer drug resistance, angiogenesis and cancer stem cell self-renewal. Adding to the complexity of this issue, non-genomic effects of TH mediated by integrin receptor on cell surface can also modulate several biological functions. Accumulating evidences indicate that regulations by genomic and non-genomic effects of TH overlap. Taken together, these observations suggest that the functions of TH depend largely on cell context, and TH/TR plays a duel role in cancer progression. Therefore, understanding the maze of biological effects of TH has become a necessity when attempting to develop effective therapeutic and preventive strategies in liver cancer.